Spatio-temporal Use of Oral Rabies Vaccines in Fox Rabies Elimination Programmes in Europe. - Thomas F Müller; Ronald Schröder; Patrick Wysocki; Thomas C Mettenleiter; Conrad M Freuling (Public Library of Science (PLoS), 2015)
In Europe, the elimination of wildlife rabies using oral rabies vaccination [ORV] of foxes for more than 30 years has been a success story. Since a comprehensive review on the scope of the different oral rabies vaccine baits distributed across Europe has not been available yet, we evaluated the use of different vaccine baits over the entire period of ORV [1978-2014]. Our findings provide valuable insights into the complexity of ORV programs in terms of vaccine related issues. More than 10 oral vaccines against rabies were used over the past four decades. Depending on many factors, the extent to which oral rabies virus vaccines were used varied considerably resulting in huge differences in the number of vaccine doses disseminated in ORV campaigns as well as in large spatial and temporal overlaps. Although vaccine virus strains derived from the SAD rabies virus isolate were the most widely used, the success of ORV campaigns in Europe cannot be assigned to a single oral rabies virus vaccine alone. Rather, the successful elimination of fox rabies is the result of an interaction of different key components of ORV campaigns, i.e. vaccine strain, vaccine bait and strategy of distribution.